MicroRNAs of Toxocara canis and their predicted functional roles. Issue 1 (December 2016) - Ma, Guangxu; Luo, Yongfang; Zhu, Honghong; Luo, Yongli; Korhonen, Pasi; Young, Neil; Gasser, Robin; Zhou, Rongqiong
Abstract Background Toxocara canis is the causative agent of toxocariasis of humans and other animals. This parasitic nematode (roundworm) has a complex life cycle, in which substantial developmental changes and switches occur. As small non-coding RNAs (sRNAs) are key regulators of gene expression in a wide range of organisms, we explored these RNAs inT. canis to provide a basis for future studies of its developmental biology as well as host interactions and disease at the molecular level. Methods We conducted high-throughput RNA sequencing and bioinformatic analyses to define sRNAs in individual male and female adults ofT. canis . Results Apart from snRNA and snoRNA, 560 and 619 microRNAs (miRNAs), including 5 and 2 novel miRNAs, were identified in male and female worms, respectively, without piRNAs being detected in either sex. An analysis of transcriptional profiles showed that, of 564 miRNAs predicted as being differentially transcribed between male and female individuals ofT. canis, 218 miRNAs were transcribed exclusively in male and 277 in female worms. Functional enrichment analysis predicted that both male and female miRNAs were mainly involved in regulating embryonic morphogenesis, hemidesmosome assembly and genetic information processing. The miRNAs differentially transcribed between the sexes were predicted to be associated with sex determination, embryonic morphogenesis and nematode larval development. The roles of miRNAs were predicted based on gene ontology (GO) and KEGG pathway annotations. The miRNAsTc -miR-2305 andTc -miR-6090 are proposed to have roles in reproduction, embryo development and larval development, andTc -let-7-5p, Tc -miR-34 andTc -miR-100 appear to be involved in host-parasite interactions. Together with published information from previous studies, some miRNAs (such asTc -miR-2861, Tc -miR-2881 andTc -miR-5126) are predicted to represent drug targets and/or associated with drug resistance. Conclusions This is the first exploration of miRNAs inT. canis, which could provide a basis for fundamental investigations of the developmental biology of the parasite, parasite-host interactions and toxocariasis as well as applied areas, such as the diagnosis of infection/disease, drug target discovery and drug resistance detection.